Peran Dewan Kemakmuran Masjid (DKM) Nurul Hikmah Dalam Meningkatkan Kegiatan Keagamaan Jamaah Masjid Nurul Hikmah - Permana, Toni Sagita; Savitri, Fania Mutiara (Tadbir: Jurnal Manajemen Dakwah FDIK IAIN Padangsidimpuan, 2024)
Mosques have a very important position in Islamic society, namely the center for the development of the people. When the ideal function has been realized, the quality of the people will experience an impressive improvement. To make this happen, of course it is necessary to create a place for people who are able to carry out the function of the mosque, such as the formation of the Mosque Prosperity Council (DKM).  The aim of this research is to obtain an in-depth picture of: 1) To find out the program carried out by the Nurul Hikmah Mosque Prosperity Council (DKM) in increasing the religious activities of the Nurul Hikmah mosque congregation, Kertajaya Village, Tanggeung District, Cianjur Regency 2) To find out the role of the Mosque Prosperity Council (DKM). ) Nurul Hikmah in increasing the religious activities of the Nurul Hikmah mosque congregation, Kertajaya Village, Tanggeung District, Cianjur Regency.This research uses qualitative research methods to obtain an in-depth understanding of the role of the Nurul Hikmah Mosque Prosperity Council (DKM) in improving the religious activities of the congregation at the Nurul Hikmah Mosque Des. Kertajaya, District. Tanggeung, Kab. Cianjur. and using qualitative data analysis techniques using an inductive mindset. The results of this research are: 1) Nurul Hikmah Mosque Prosperity Council (DKM) Program in Increasing Religious Activities of the Nurul Hikmah Mosque Congregation, recitation program, PHBI, management of corpse care, coaching youth activities at the mosque and compensation for orphans... 2) The role of the Mosque Prosperity Council (DKM) Nurul Hikmah in increasing the religious activities of the Nurul Hikmah Mosque congregation Des. Kertajaya, District. Tanggeung Regency Cianjur, by carrying out religious programs such as: Managing all mosque activities, unifying the Muslim community, revitalizing the spirit of deliberation, fortifying the faith of the community and building congregational solidarity.